2018
DOI: 10.3390/nu10111661
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake in Population with Metabolic Syndrome: Is the Prevalence of Inadequate Intake Influenced by Geographical Area? Cross-Sectional Analysis from PREDIMED-Plus Study

Abstract: Inadequate diet influences chronic diseases such as cardiovascular disease (CVD), the leading cause of death in Spain. CVD figures vary from one geographical region to another; this could be associated with different food choices. Our aim was to analyse the influence of geographical area on nutrient intakes among the Spanish adult population with Metabolic Syndrome (MetS). We analysed cross-sectional baseline data from the PREDIMED-Plus study: 6646 Spanish adults, aged 55–75 years, with overweight/obesity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Vegetable consumption according to the recommendations was low (17.0%), coinciding with the consumption data of the Spanish population, where it was indicated that, although it is the elderly population that consumes the most vegetables, Cantabria is the Spanish region where vegetable consumption is the lowest [ 39 ]. This also coincides with the results of the PREDIMED-Plus study [ 85 ], according to which vegetable consumption in the northern area was significantly lower than in the other areas studied. Vegetable consumption was higher in women (21.1%) relative to men (10.7%, p < 0.05; Table S1 ), which could be related to the fact that it is common for women to make dietary modifications with the objective of body weight control, significantly raising their vegetable consumption relative to men [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Vegetable consumption according to the recommendations was low (17.0%), coinciding with the consumption data of the Spanish population, where it was indicated that, although it is the elderly population that consumes the most vegetables, Cantabria is the Spanish region where vegetable consumption is the lowest [ 39 ]. This also coincides with the results of the PREDIMED-Plus study [ 85 ], according to which vegetable consumption in the northern area was significantly lower than in the other areas studied. Vegetable consumption was higher in women (21.1%) relative to men (10.7%, p < 0.05; Table S1 ), which could be related to the fact that it is common for women to make dietary modifications with the objective of body weight control, significantly raising their vegetable consumption relative to men [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Women with MetS showed more energy intake from protein than those without MetS (18% vs. 16.9%, respectively) ( p < 0.01), but both were within recommended ranges [26,27]. A similar nutrient distribution among Spanish population with MetS [32] and healthy adults has been previously shown [8]. Differences were also previously observed between subjects with and without MetS for total energy intake, sugar intake, dietary glycemic load, percentage of dietary protein, PUFA, and fiber intake [33].…”
Section: Discussionmentioning
confidence: 99%
“…Total sugar intake was also quantified in the ANIBES study: results were higher in children (17.18%) and adolescents (16.33%) and markedly lower in adults (15.34%) and older adults (12.97%) [8]. The inhabitants of Northern Spain, especially men, consumed more sugar and sweets than adult from other Spanish areas [32]. Conversely, the World Health Organization (WHO) recommended <10% of energy intake be provided by sugars [34], whereas <5% has been recommended in the United Kingdom [35].…”
Section: Discussionmentioning
confidence: 99%
“…Research aimed at evaluating the combined benefits achieved by associating the Mediterranean eating pattern with systematic induction of weight loss is also under way. A large randomized clinical trial, PREDIMED-PLUS, conducted by the same team of Spanish investigators as PREDIMED and using the same type of Mediterranean-style dietary interventions combined with a three-point weight-loss intervention consisting of restriction of energy intake, physical activity recommendations, and behavioral modifications, finished randomization of 6874 participants in December 2016 and is expected to close in March 2022; design of the study, some baselines, and cross-sectional analyses in PREDIMED-PLUS have recently been published [102,103,104,105,106].…”
Section: The Mediterranean Diet Nowadays: Between Cultural Erosionmentioning
confidence: 99%